A multi-faceted approach to analyzing historical police logs: a research note - Wells, Jamin (Policing and society, 2025)
This research note provides an exploratory analysis of a remarkable – and broadly available – set of documents from the early twentieth century. This preliminary study examined one month of police call logs and warrant books from Pensacola, Florida, in December 1912. Combining perspectives from history, geography, and police practice, the authors integrated these records with digitised spatial data using Geographic Information System (GIS). The analysis revealed significant racial disparities in arrest patterns, unexpected temporal trends in policing activity, and compelling spatial concentrations of law enforcement interactions. This project suggests the potential of applying modern analytical techniques to historical police datasets in order to yield meaningful insights into the evolution of policing practices and their societal impacts. It highlights the wealth of untapped historical arrest records available for similar studies across the United States, suggesting avenues for future comparative research that bridges historical analysis with contemporary policing concerns.